Influence of the Catalyst Particle Size on the Aqueous Phase Reforming of n-Butanol Over Rh/ZrO2 - Harju, Heikki; Pipitone, Giuseppe; Lefferts, Leon (Frontiers in Chemistry, 2020)
Butanol is a by-product obtained from biomass that can be valorized through aqueous phase reforming. Rh/ZrO2 catalysts were prepared and characterized, varying the size of the support particles. The results showed a relatively mild effect of internal mass transport on butanol conversion. However, the influence of internal transport limitations on the product distribution was much stronger, promoting consecutive reactions, i.e. dehydrogenation, hydrogenolysis and reforming of propane and ethane. Hydrogen consuming reactions, i.e. hydrogenolysis, were more strongly enhanced than hydrogen producing reactions due to internal concentration gradients. Large support particles deactivated faster, attributed to high concentrations of butyraldehyde inside the catalyst particles, enhancing deposit formation via aldol condensation reactions. Consequently, also the local butyric acid concentration was high, decreasing the local pH, enhancing Rh leaching. The influence of internal transfer limitation on product distribution and stability is discussed based on a reaction scheme with three main stages, i.e. (1) formation of liquid intermediates via dehydrogenation, (2) formation of gas via decarbonylation/decarboxylation reactions and (3) hydrocarbon hydrogenolysis/reforming/dehydrogenation.